Exploring the Impact of Mental Fatigue and Emotional Suppression on the Performance of High-Intensity Endurance Exercise. Issue 4 (August 2022) - Schlichta, Clara; Cabral, Luana Loss; da Silva, Caroline Kemela; Bigliassi, Marcelo; Pereira, Gleber
This study investigated the extent to which mental fatigue and emotional suppression affected exercise endurance. Twelve participants performed cycling endurance tests at 80% of their peak power up to the point of exhaustion. Two experimental conditions (mental fatigue [MF] and emotion suppression conditions [ES]) and a control condition (CO) were administered. Participants responded to psychological measures throughout the exercise trials. Both MF and ES conditions hindered exercise performance relative to the CO, and there was no statistically significant difference between the negative effects of both MF and ES conditions. Of note, however, higher levels of subjective fatigue were reported in MF, prior to commencing the exercise test. High cognitive loads that induce MF and/or engaging in ES may reduce high intensity endurance exercise performance among young adults, but further research with greater numbers of participants is needed to replicate and extend these findings.